المحاسبة عن المسؤولية الاجتماعية والإفصاح عنها في القوائم المالية – عرض لمجموعة من النماذج- - عبد اللاوي, يحي; فوحمة, يامن; نصيرة, بلال (جامعة الوادي - University of Eloued, 2020)
هدفت الدراسة إلى بيان مفهوم المحاسبة عن المسؤولية الاجتماعية من خلال عرض المفاهيم المتعلقة بها وأهدافها ومجالاتها وبيان طرق ونماذج الإفصاح عن التكاليف والمنافع الاجتماعية على مستوى القوائم المالية للمؤسسات التي تتبنى مبادئ المسؤولية الاجتماعية، حيث خلصت الدراسة إلى مجموعة من النتائج كما يلي: تعتبر المحاسبة عن المسؤولية الاجتماعية من أحدث الفروع في المحاسبة وتعرّف على أنها منهج لقياس وتوصـيل المعلومـات المترتبة على قيام الإدارة بمسؤولياتها الاجتماعية لمختلف الطوائف المستفيدة داخل المجتمع، بشكل يمكـن مـن تقييم الأداء الاجتماعي للمشروع, كما أن هناك العديد من نماذج الإفصاح المحاسبي عن المسؤولية الاجتماعية منها ما يتبنى طريقة عرض المعلومات الاجتماعية في تقارير منفصلة عن القوائم المالية التقليدية، كقائمة الدخل وقائمة التأثير الاجتماعي وقائمة النشاط الاجتماعي-الاقتصادي، ومنها من يتبنى طريقة عرضها مندمجة مع المعلومات المالية في القوائم المالية التقليدية، ككشف العمليات الجارية الاقتصادية- الاجتماعية. The study aimed to clarify the concept of accounting for social responsibility by presenting concepts related to it, its goals and fields, and showing methods and models for disclosing social costs and benefits at the level of financial statements of institutions that adopt the principles of social responsibility. The study concluded a set of results as follows: Accounting for social responsibility is one of the most recent branches of accounting and it is defined as an approach for measuring and communicating information resulting from the administration's social responsibilities to the various benefiting communities within society; In a way that enables the social performance of the project to be evaluated, and there are many forms of accounting disclosure for social responsibility, including those that adopt a method of presenting social information in separate reports on traditional financial statements, such as the income list, the social impact list and the list of socio-economic activity, and among those who adopt the method of presentation Combined with financial information in traditional financial statements, such as the disclosure of ongoing socio-economic processes
Social Responsibility Accounting and disclosure in the financial statements - a set of models - presentation
مقال
Keywords: المسؤولية الاجتماعية، محاسبة المسؤولية الاجتماعية، الإفصاح المحاسبي، القوائم المالية; Social Responsibility; Social Responsibility Accounting; Accounting disclosure; financial statements